Left Ventricular Noncompaction Cardiomyopathy Managed with Cardiac Resynchronization Therapy: A Case Report - Mainak Mukhopadhyay; Pradipta Som; Rajkumar Mondal; Pinaki Maiti; Nandini Chatterjee (Bengal Physician Journal)
Although “spongy myocardium” was first observed by Grant in 1926, left ventricular noncompaction (LVNC) cardiomyopathy was originally described by Engberding and Bender in 1984.1 Left ventricular noncompaction cardiomyopathy is characterized by abnormal ventricular myocardial protrusions with a thin layer of properly compacted myocardium.2,3 It is a rare entity, with a prevalence less than 0.02%.4 We report a case of LVNC cardiomyopathy with dyssynchrony, which was successfully managed with cardiac resynchronization therapy (CRT).